Nymphs in foraging populations of Coptotermes gestroi (Isoptera: Rhinotermitidae) - Albino, Erica [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Brill Academic Publishers, 2011)
Food searching activity by subterranean termites involves workers, soldiers and nymphs. The present study was carried out for elucidating aspects of nymph foraging behavior in Brazil where the species Coptotermes gestroi (Wasmann, 1896) is exotic. Monitoring was conducted through making regular collections from seven different colonies for a period of 22 months, which exhibited the production of forager nymphs all year round. A biometric study was conducted to determine the instars of the forager nymphs collected. The identification of male and female nymphs was also conducted for establishing the sex proportion, which was slightly male-biased. From the 533 forager nymphs collected, 34 were from the 3rd instar, 280 from the 4th instar and 219 from 5th instar. The results suggest that 3rd instar nymphs were not too active in the foraging activities because they were collected only in one colony and in an insignificant quantity. (C) Koninklijke Brill NV, Leiden, 2011.
Keywords: Nymphal instar; subterranean termite; forager nymph; Coptotermes gestroi